2019
DOI: 10.1136/tobaccocontrol-2019-055195
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to tobacco marketing in bars predicts subsequent use of multiple tobacco products among non-tobacco-using college students

Abstract: BackgroundDue to other marketing restrictions, one venue where tobacco companies concentrate their marketing efforts to reach young adults is bars/nightclubs.ObjectiveThis study examined the relationship between exposure to tobacco marketing in bars/nightclubs and number of alternative tobacco/nicotine products used 6 months later among college students.MethodsParticipants were 1,406 students aged 18–29 years old who reported going to bars or nightclubs at least rarely (M age=21.95; 67% female; 46% non-Hispani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…They have also been used to encourage young people to engage with tobacco brands through free cigarettes, merchandise and competitions; create a social environment that promotes smoking trials and collect consumer data on patrons 18. Studies from high-income countries have shown that young people were exposed to individual sales promotions in bars and clubs,19 and that exposure to these promotions was associated with an increased risk of smoking uptake 20 21…”
Section: Introductionmentioning
confidence: 99%
“…They have also been used to encourage young people to engage with tobacco brands through free cigarettes, merchandise and competitions; create a social environment that promotes smoking trials and collect consumer data on patrons 18. Studies from high-income countries have shown that young people were exposed to individual sales promotions in bars and clubs,19 and that exposure to these promotions was associated with an increased risk of smoking uptake 20 21…”
Section: Introductionmentioning
confidence: 99%
“…Poly tobacco use can be influenced by several marketing techniques. Use of poly tobacco products has increased in recent years given the novelty of some of the products and marketing directed at young adults [24][25][26]. A study by Herrera et al [24], found that increased exposure to free samples and marketing from the tobacco industry at night clubs/bars increased the number of products used among non-tobacco users 6 months later.…”
Section: Discussionmentioning
confidence: 99%
“…Use of poly tobacco products has increased in recent years given the novelty of some of the products and marketing directed at young adults [24][25][26]. A study by Herrera et al [24], found that increased exposure to free samples and marketing from the tobacco industry at night clubs/bars increased the number of products used among non-tobacco users 6 months later. Another study found that advertising of any tobacco product on Reddit (social media site) increased the odds for e-cigarette use among young adults [25,27].…”
Section: Discussionmentioning
confidence: 99%
“…(Esterberg and Compton, 2005;Ismailov and Leatherdale, 2010;Lucksted et al, 2000;Missen et al, 2013) These practices hinder NRT sale and by its virtue, tacitly promote e-cigarettes as they are placed on top of the counter. (Herrera et al, 2019) The overall range of prices for e-cigarettes was £19 (£10.99 to £29.99) vs £31.74 for NRT (£4.25 to £35.99) potentially make e-cigarettes more affordable, per-unit of equivalent bioavailable nicotine.…”
Section: No Patient and Public Involvementmentioning
confidence: 99%